Lipoic acid metabolism in Escherichia coli: isolation of null mutants defective in lipoic acid biosynthesis, molecular cloning and characterization of the E. coli lip locus, and identification of the lipoylated protein of the glycine cleavage system. - Vanden Boom, T J (1991)
We report the isolation and genetic characterization of novel Tn10dTc and Tn1000dKn insertion mutations in and near the lip locus of the Escherichia coli chromosome. The Tn10dTc and Tn1000dKn mutations define two genes, lipA and lipB, involved in lipoic acid biosynthesis. Two representative alleles (lip-2 and lip-9) from the previously reported genetic class of lipoic acid auxotrophic mutants (A. A. Herbert and J. R. Guest, J. Gen. Microbiol. 53:363-381, 1968) were assigned to the lipA complementation group. We have cloned the E. coli lip locus and developed a recombinant plasmid-based genetic system for fine-structure physical-genetic mapping of mutations in this region of the E. coli chromosome. We also report that a recombinant plasmid containing a 5.2-kbp PvuII restriction fragment from the E. coli lip locus produced three proteins of approximately 8, 12, and 36 kDa by using either a maxicell or in vitro transcription translation expression system. The 36-kDa protein was identified as the gene product encoded by the lipA locus. Finally, we have identified a previously unreported lipoylated protein that functions in the glycine cleavage system of E. coli.